PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN AUGMENTED REALITY TERHADAP HASIL BELAJAR PADA MATERI AKIDAH AKHLAK - Cecep Sobar Rochmat; Afifah Niyafatin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was conducted to improve students’ learning outcomes. Based on the existing scores, students’ learning outcomes have not yet met the expected Minimum Mastery Criteria (KKM). Therefore, field research was carried out to determine the difference between previous learning outcomes and the current implementation. The purpose of this study is to determine the effect of Augmented Reality learning media on learning outcomes in the Akidah Akhlak subject for fourth-grade students at MI Tarbiyatul Banin Pati, Central Java. The method used in this research is quantitative experimental research with a Quasi-Experimental Design in the form of a Nonequivalent Control Group Design. The research sample consisted of two classes: the experimental class, which received learning using Augmented Reality media, and the control class, which used PowerPoint-based learning methods. The instrument used was a learning achievement test in the form of pre-test and post-test, which had been tested for validity and reliability. Data analysis was carried out using prerequisite tests, including normality and homogeneity tests, followed by the t-test (Independent Sample t-test) to examine the difference in average learning outcomes between the experimental and control classes. The t-test significance value showed 0.006, indicating that the use of Augmented Reality learning media has a significant and positive effect on improving Akidah Akhlak learning outcomes for fourth-grade students at MI Tarbiyatul Banin Pati.